Is the Marginal Effect of Education on Income Diminishing? - Shahor, Tal (European Journal of Economics and Business Studies, 2018)
This study seeks to determine the effect of education on income for wage workers in Israel, for the years 2005 – 2015. The hypothesis of this study is that the marginal effect of the number of years of education on income will be declining, such that at a certain point, it will be zero or even negative. The results of the study show that until 2012, the marginal effect of the number of years of education on income is linear. However, beginning in 2013, the marginal effect of the number of years of education on income is declining.
Keywords: Education; Income; Wage; Israel; Age.